Observation of cavity-tunable topological phases of polaritons - Dong Zhao; Ziyao Wang; Linyun Yang; Yuxin Zhong; Xiang Xi; Zhenxiao Zhu; Xiaoyuan Jiao; Qing-an Tu; Yan Meng; Bei Yan; Ce Shang; Zhen Gao (Nature Communications)
Abstract Topological polaritons characterized by light-matter interactions have become a pivotal platform for exploring new topological phases of matter. Recent theoretical advances unveiled a novel mechanism for tuning the topological phases of polaritons by modifying the surrounding photonic environment (light-matter interactions) without altering the lattice structure. Here, by embedding a dimerized chain of microwave helical resonators within a metallic cavity, we report the experimental observation of tunable topological phases of polaritons by varying the cavity width, which governs the strength of light-matter interactions. Moreover, we experimentally verified a previously predicted new type of topological phase transition, including three noncoincident critical points in the parameter space: the closure of the polaritonic bandgap, the transition of the Zak phase, and the hybridization of the topological edge states with the bulk states. Our experimental results reveal some unobserved properties of topological phases of matter when strongly coupled to light and provide a new design principle for tunable topological photonic devices.